The Irrelevance of the Security Dilemma for Civil Wars - Duyvesteyn, I.G.B.M.; Visser, E. (Routledge, 2014)
This article revisits the security dilemma theory and its application to civil conflict. Based on a careful reading of existing studies, it exposes the deviations from the original theory developed in the 1950s and more recent amendments, which have substantially reduced the explanatory value of the theory. The article shows that when the original and the amended versions of the theory are applied to civil conflict, neither can explain the outbreak of armed conflict. While anarchy might be present as a precondition for the dilemma to operate, a previous history of violent interaction often leaves little room for misperception of intentions. Absent uncertainty about malign intentions toward the other group, the security dilemma theory loses relevance to explain the outbreak of civil conflict.
Keywords: SDG 16 - Peace, Justice and Strong Institutions